P63-F Time perception and reactivity to photo- and phono-stimulation in patients with chronic vascular ischemia - Portnova, Galina (Clinical neurophysiology, 2019)
The process of normal aging is usually accompanied by the expected changes in time perception that could be modified in patients with chronic vascular ischemia (CVI). The EEG of the investigated group of patients sometimes could be hardly differentiated with the normal EEG and requires provoking techniques. We presented the 2, 4, 8 and 16 Hz photo- and phono-stimulation during EEG recording, accompanied by the cognitive testing of time perception, to 3 groups of healthy subjects: young, middle-aged and old, and to patients with chronic vascular ischemia. We found that in healthy elderly subjects compared to younger individuals had higher reactivity to phono-stimulation, which correlated with the underestimating of 10-s intervals. The patients with the CVI had higher reactivity to 2 and 4 Hz photo-stimulation compared to other groups. Meanwhile, the reactivity to 8 and 16 Hz photo-stimulation was higher only in patients with CVI who overestimated 10-s intervals.